Penerapan Media Pembelajaran Interaktif Quizwhizzer dengan Metode Diferensiasi Pembelajaran untuk Meningkatkan Hasil Belajar Siswa di SMK Muhammadiyah 2 Kuningan - Riana, Fadil Eka; Setiawan, Dena Latif (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to improve student learning outcomes in Computer Fundamentals subjects by using the learning differentiation method using quizwhizzer interactive media. This study uses the pre-experiment method with the research design used is